Urinary kallikrein: mechanisms of its release and action. (Review and hypothesis) - Martínez Seeber, Alejandro (Investigación Clínica, 2013)
Urinary kallikrein is originated in the kidney. In this review it is postulated that urinary kallikrein excretion is related with the necessity to eliminate water. The principal releasing mechanism is a wash-out effect on renal kallikrein, produced by the flow reaching the tabular distal cell. Several systems can modify kallikrein excretion acting on the mechanisms of its release and/or synthesis. Urinary kallikrein regulates extracellular space inhibiting water distal reabsorption.